Transcranial Doppler during the first week after cardiac arrest and association with 6-month outcomes - Reichenbach, Antje; Alteheld, Lars; Henriksen, Julia; Nakstad, Espen Rostrup; Andersen, Geir Øystein; Sunde, Kjetil; Šaltytė Benth, Jūratė; Lundqvist, Christofer (Frontiers in Neurology, 2023)
Background: Early prediction of outcome in comatose patients after out-of-hospital cardiac arrest is challenging. Prognostication tools include clinical examination, biomarkers, neuroradiological and neurophysiological tests. We studied the association between transcranial doppler (TCD) and outcome.This was a predefined sub-study of the prospective observational Norwegian Cardiorespiratory Arrest Study. Patients underwent standardized post resuscitation care, including target temperature management (TTM) to 33°C for 24 hours. TCD was performed at day 1, 3 and 5-7. Primary endpoint was cerebral performance category (CPC) at 6 months, dichotomized into good (CPC 1-2) and poor (CPC 3-5) outcome. We used linear mixed modelling time-series analysis.Results: Of 139 TCD-examined patients, 81 (58%) had good outcome. Peak systolic velocity in the middle cerebral artery (PSV) was low during TTM (day 1) and elevated after rewarming (day 3). Thereafter it continued to rise in patients with poor, but normalized in patients with good outcome. At day 5-7, PSV was 1.0 m/sec (95% CI 0.9; 1.0) in patients with good outcome versus 1.3 m/sec (95% CI 1.1; 1.4) in patients with poor outcome (p<0.001) Conclusion: Elevated PSV at day 5-7 indicated poor outcome. Our findings suggest that serial TCD examinations during the first week after cardiorespiratory arrest may improve our understanding of serious brain injury.